WHY EBERL IS WRONG. REFLECTIONS ON THE BEGINNING OF PERSONHOOD - Deckers, Jan (Bioethics, 2007)
In a paper published in Bioethics, Jason Eberl has argued that early embryos are not persons and should not be granted the status possessed by them.1 Eberl bases this position upon the following claims: (1) The early embryo has a passive potentiality for development into a person. (2) The early embryo has not established both ‘unique genetic identity’ and ‘ongoing ontological identity’, which are necessary conditions for ensoulment. (3) The early embryo has a low probability of developing into a more developed embryo. This paper examines these claims. I argue against (1) that a plausible view is that the early embryo has an active potentiality to grow into a more developed embryo. Against (2), I argue that neither ‘unique genetic identity’ nor ‘ongoing ontological identity’ are necessary conditions for ensoulment, and that ‘ongoing ontological identity’ is established between early embryos and more developed embryos. Against (3), I argue that the fact that the early embryo has a low probability of developing into a more developed embryo, if true, does not warrant the conclusion that the early embryo is not a person. If Eberl is right that the human soul is that which organises the activities of a human being and that ensouled humans are persons, embryos are persons from conception.